If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -92 = -1x + 169 Reorder the terms: -92 + 8x = -1x + 169 Reorder the terms: -92 + 8x = 169 + -1x Solving -92 + 8x = 169 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -92 + 8x + x = 169 + -1x + x Combine like terms: 8x + x = 9x -92 + 9x = 169 + -1x + x Combine like terms: -1x + x = 0 -92 + 9x = 169 + 0 -92 + 9x = 169 Add '92' to each side of the equation. -92 + 92 + 9x = 169 + 92 Combine like terms: -92 + 92 = 0 0 + 9x = 169 + 92 9x = 169 + 92 Combine like terms: 169 + 92 = 261 9x = 261 Divide each side by '9'. x = 29 Simplifying x = 29
| v^2+64=0 | | 19+5x=3(4x+9) | | z+5=-21 | | 5x-50+5x=570 | | 5x^2-3x-9-(2x^2+x-6)= | | 2(x+6)+4(x+4)= | | y=3f(x) | | 4x+16+4x=392 | | (-12)-8= | | 9+t=36 | | 4x-8sqrtx-5=0 | | 3x-30=2x+15 | | 14X^2+20X-16=0 | | 2(3c+7)=-25-9c | | 2w^2+14w-240=0 | | -2(4x+3)+5x=9 | | 72X^2-5X-25=0 | | 3(x+9)=4x+3 | | 9+5c=45+2x | | 104=y-4 | | 2X^2-xy-6y^2=0 | | 9u+1=46 | | 36X^2-18X+2=0 | | 25-13=4(x-5) | | 7b-2+9=-19 | | 7y-(16y+2)=4 | | x^2-4x-8y+20=0 | | 3x-21+4x=273 | | 9(1-3n)=-34 | | (8x-3)+(2x+5)-(6-x)= | | 10x^2+12x-64=0 | | -5k-8=6-17 |